Spatial receptive field properties of lateral geniculate cells in the owl monkey (Aotus azarae) at different contrasts: a comparative study - Kilavik, B.E.; Silveira, L. C. L.; Kremers, Jan (European Journal of Neuroscience, 2007)
Several physiological properties of owl monkey lateral geniculate nucleus (LGN) cells were studied to verify whether its nocturnal habit has an influence on the organization of its subcortical visual system. Receptive field (RF) dimensions were measured using drifting gratings and bipartite field stimuli. We found that owl monkey cells LGN have larger RFs and were on average more non-linear than those of diurnal monkeys. But, as in other anthropoids, there is an increase in RF centre size with increasing eccentricity, and there is a limited correlation between these centre sizes and retinal ganglion cell dendritic tree sizes. The influence of contrast on sizes and peak sensitivities of RF centres and surrounds and on the response phases was studied. Both the sizes and peak sensitivities of the RF centres and surrounds decrease as contrast increases. As a result, the responses to low spatial frequency stimuli saturate with increasing contrast. Estimates of contrasts at half-maximal responses confirm the presence of saturation. It was found that the magnocellular cells saturate more strongly than parvocellular cells. The response phase increases with increasing contrast. These data resemble those obtained in the common marmoset, indicating that these are basic features of the primate visual system. We conclude that during evolution and as an adaptation to a nocturnal lifestyle, cells in the owl monkey LGN display an increased spatial integration in comparison with diurnal primate species, without a change in the basic organization common to the primate subcortical visual system.
Keywords: contrast sensitivity; koniocellular; lateral geniculate nucleus; magnocellular; parvocellular; primates